Penerapan Hukum Terhadapan Tindakan Building Pad Headphone ditinjauh dari Kekayaan Intelektual - Iwan Sandi Pangarso (Universitas Muhammadiyah Gresik, 2020)
The development of science and technology to date has spread throughout the world in a current called globalization. With globalization it has an influence on increasingly advanced lives, with the existence of information and communication products. Information technology in its fulfillment of people's needs has undergone many changes from analog to digital as it is today. One of the most important elements in the journey of every civilization is technological progress, especially communication technology. It is inconceivable how communication technology has changed human life, especially what is called a cellphone (cellphone). Almost everyone now has and uses mobile phones in communication activities. Likewise with telecommunication equipment for mobile phones (mobile phones), it has developed so rapidly from being only used for telephones and sending text or text messages, to those that can be used to listen to music, radio, for the internet, watch television, and so on. Today, people have considered it mandatory to have telecommunications equipment for mobile phones (cellphones) so that it is natural for someone to have more than one handphone. Likewise, cellular telephone operators in Indonesia continue to compete to provide the best service for their users.